1999
DOI: 10.1177/096120339900800511
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol prevents and testosterone promotes Fas-dependent apoptosis in CD4+ Th2 cells by altering Bcl 2 expression

Abstract: Coxsackievirus B3 (CVB3) induces myocarditis in male BALB/c mice. Female mice are resistant to viral myocarditis, except in the third trimester of pregnancy and postpartum. Cardiac damage is mediated by T lymphocytes activated during virus infection. Th1 (interferon-gamma+) cell responses promote cardiac injury, while disease resistance correlates to preferential activation of Th2 (interleukin-4+) cell responses. CVB3-specific Th1 and Th2 cell clones were established, treated with between 0 and 100 ng/ml 17bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 19 publications
4
48
0
Order By: Relevance
“…Such effects may be mediated through any of several mechanisms described in other rodents. In mice, castration increases thymus size and proliferation of T lymphocytes (10,36), and testosterone reverses these effects (11,36) through a direct action on membrane-bound androgen receptors (2,25). Testosterone induces apoptosis in CD4ϩ and CD4ϩCD8ϩ lymphocytes, in part by increasing production of the proinflammatory cytokine TNF-␣ (23).…”
Section: Discussionmentioning
confidence: 99%
“…Such effects may be mediated through any of several mechanisms described in other rodents. In mice, castration increases thymus size and proliferation of T lymphocytes (10,36), and testosterone reverses these effects (11,36) through a direct action on membrane-bound androgen receptors (2,25). Testosterone induces apoptosis in CD4ϩ and CD4ϩCD8ϩ lymphocytes, in part by increasing production of the proinflammatory cytokine TNF-␣ (23).…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Consistent with the decrease of TNF-␣ and IFN-␥ production in cardiac allografts, local overexpression of Bcl-2 resulted in the reduced expression of ICAM-1 and VCAM-1. In addition, Huber et al 39 recently reported that increased Bcl-2 expression on T H 2 cells led to the selective survival of T H 2 cells in the mouse viral myocarditis model. In contrast, we show that the local overexpression of Bcl-2 in cardiac allografts has a significant influence on T H 1-type immune responses but not on T H 2-type immune responses.…”
Section: Org Frommentioning
confidence: 99%
“…Figure 5 shows the percentages of cells -10 -8 M) of 17β-estradiol might slightly increase the cells not stimulated by mitogen in the late phase of apoptosis. Some previous reports 33,34) said that the low-level 17β-estradiol suppressed lymphocyte apoptosis. It might be suggested that 17β-estradiol prevents the change of membrane conformation between the late apoptotic phase and the final debris phase.…”
Section: Resultsmentioning
confidence: 93%